Pengaruh Penambahan Aditif Diethanolamine (DEA) terhadap Energi Celah Pita TiO₂ Terdoping ZnO menggunakan Metode Sol-Gel - Sri Rara Julianti; Hary Sanjaya (MASALIQ, 2025)
This study aims to evaluate the effect of Diethanolamine (DEA) addition on the band gap energy and crystal structure of TiO₂ semiconductors doped with ZnO using the sol-gel method. DEA functions as a stabilizing agent and particle growth controller to achieve more uniform particle size and distribution. DEA concentrations of 1%, 2%, 3%, 4%, and 5% were applied. The synthesis process involved mixing TiO₂ and ZnO in ethanol, adding DEA, sonication, drying, and calcination. Characterization was conducted using UV-Vis Diffuse Reflectance Spectroscopy (UV-DRS), employing the Kubelka-Munk approach to determine the band gap values. The results indicate that DEA addition significantly reduced the band gap energy to 3.05 eV at the optimal concentration of 4%, attributed to the formation of structural defects and reduced particle size, which expanded the active surface area and shortened the electron excitation distance. However, at 5% DEA concentration, the band gap increased to 3.14 eV due to particle agglomeration. These findings confirm the crucial role of DEA in controlling the optical properties of TiO₂-ZnO, with a 4% concentration offering optimal performance for photocatalytic and solar cell applications. This study demonstrates that chemical additive manipulation during synthesis is an effective strategy for engineering the electronic properties of semiconductors.